The making of a Roman imperial estate : archaeology in the Vicus at Vagnari, Puglia - Carroll, Maureen, (Archaeopress Roman archaeology ;, 2022)
'The Making of a Roman Imperial Estate' presents excavations and analysis of material remains at Vagnari, in southeast Italy, which have facilitated a detailed and precise phasing of a rural settlement, both in the late Republican period in the 2nd and 1st centuries BC, when it was established on land leased from the Roman state after Rome's conquest of the region, and when it became the hub (vicus) of a vast agricultural estate owned by the emperor himself in the early 1st century AD. This research addresses a range of crucial questions concerning the nature of activity at the estate and the changes in population in this transitional period. It also maps the development of the vicus in the 2nd and 3rd centuries AD, shaping our understanding of the diversity and the mechanics of the imperial economy and the role of the vicus and its inhabitants in generating revenues for the emperor.